Expressão da proteína γH2AX e 8-OHdG em glândula salivar parótida de ratos expostos a radiação X - Biaggi, Guilherme Felício de [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The parotid salivary gland is a radiation-sensitive organ and is often found to be incidentally exposed in the area of x-ray and tomography studies of the head and neck. Exposure to low dose ionizing radiation can cause cell damage leading to changes in genetic material. Double strand ruptured DNA damage is observed by immunohistochemistry, by the presence of phosphorylated histone H2AX (γH2AX) protein in the cell nucleus. Morphologically, individual dots (punctual focal points) are visualized by the concentration of γH2AX proteins. The residence time of these pooled foci in cells demonstrates the efficiency or otherwise of the DNA tape repair process. Exposure to radiation can also cause indirect damage by the action of reactive oxygen species (ROS). EROS lesions the DNA strand by forming the oxidized 8-hydroxy-2'-deoxyguanosine (8-OHdG) molecules. The objective of the present study was to analyze the radiosensitivity of the parotid gland of rats exposed to X radiation, emitted by the radiographic dental apparatus, in the dose corresponding to 0.1 Gray. The test groups consisted of a control group (before exposure to radiation), two hours, 24 hours and one week after X-ray exposure. Tissue biopsies were paraffin-embedded for the preparation of histological slides and immunohistochemical analysis of γH2AX and 8-OHdG. The ductal cells of the parenchyma of the parotid gland after exposure to the low dose of X radiation showed in the group two hours, significant radiosensitivity that, during the analysis period, reestablished the groups of 24 hours and one week, when compared to the control group. The immunoreactivity of 8-OHdG protein in ductal cells also showed a similar effect between the experimental groups. The cells of the glandular ducts (intercalated, striated...

A glândula salivar parótida é um órgão sensível à radiação e, com frequência, encontra-se incidentalmente exposta na área de estudos radiográficos e tomográficos de cabeça e pescoço. A exposição à baixa dose de radiação ionizante, pode causar lesões nas células levando alterações ao material genético. Danos de ruptura da dupla fita do DNA são observados por imuno-histoquímica, pela presença da proteína histona H2AX fosforilada (γH2AX), no núcleo da célula. Morfologicamente, visualiza-se pontos individuais (focos pontuais) corados, pela concentração das proteínas γH2AX. O período de permanência desses focos pontuais nas células demonstra a eficiência ou não do processo de reparo da fita do DNA. A exposição à radiação também pode causar danos indiretos, pela ação de espécies reativas de oxigênio (EROs). As EROS lesam a fita do DNA por formarem as moléculas oxidadas de 8-hidroxi-2'-desoxiguanosina (8-OHdG). O objetivo do presente trabalho foi analisar a radiossensibilidade da glândula parótida de ratos expostos à radiação X, emitida pelo aparelho radiográfico odontológico, na dosagem correspondente a 0,1 Gray. Os grupos de análise foram constituídos de grupo controle (antes da exposição à radiação), duas horas, 24 horas e uma semana após a exposição à radiação X. Biópsias teciduais foram blocadas em parafina para confecção de lâminas histológicas e análise imunoistoquímica das proteínas γH2AX e 8-OHdG. As células ductais do parênquima da glândula parótida após a exposição à baixa dose de radiação X, mostraram no grupo duas horas, radiossensibilidade significante que no decorrer do período de análise, se reestabeleceram não diferindo, os grupos de 24 horas e o de uma semana, quando comparados com o grupo controle. A imunorreatividade da proteína 8-OHdG nas células...
Keywords: Radiação ionizante; Imuno-histoquímica; Glândula parótida; Glândulas salivares; Raios X; Radiation, Ionizing